PROJECT PLANNING PROYEK PEMBANGUNAN GEDUNG I IGD RSUD PROF. DR. SOEKANDAR MOJOSARI KABUPATEN MOJOKERTO - Widianto, Ilham Najibi; Utoyo, Suselo; Zettyara, Devi (Prokons: Jurnal Teknik Sipil, 2024)
The construction project of the Emergency Room I Building at Prof. Dr. Soekandar Mojosari Hospital, with an area of 792 m², is located in Mojosari District, Mojokerto Regency, East Java, given the limited project land and the necessity to dismantle the existing IGD building, it is essential to plan the project in a timely, cost effective, and high quality manner. The objective of this thesis to provide optimal solutions to organizational structure, site layout and traffic management, strategy and implementation methods, construction work quality plan (RMPK), construction safety plan (RKK), project implementation scheduling and implementation cost budget plan (RAP). In order to compile a work breakdown structure (WBS), organizational structure, site layout and traffic management, strategy and implementation method it is necessary to obtain shop drawings and work plans and requirements. The cost budget plan (RAB), regional unit price of Mojokerto Regency 2023 and Permen PUPR No. 08 2023 are used to compile an analysis of work unit prices (AHSP) using the Microsoft Excel 2019. The preparation implementation schedule using Microsoft Project 2019. This thesis presents a discussion on the following topics the functional organizational structure is led by the project manager. The site layout is based on the calculation of the safety index and the traveling distance, as well as the management of traffic there are two access points in and ou t of the project. The project using bottom-up method. The quality is based on the quality plan, and each work item refers to the technical specifications and quality targets. A occupational health and safety is prepared, comprising construction safety objectives and policies, HSE equipment, a hazard identification, a risk assessment, a determination of risk control, and opportunities (HIRADC) and HSE program. The implementation time is 119 days. Total implementation budget plan is IDR. 7.251.064.191.